First principles investigations on the electronic structure of anchor groups on ZnO nanowires and surfaces - Dominguez, A.; Lorke, M.; Schoenhalz, A. L.; Rosa, A. L.; Frauenheim, Th; Rocha, A. R. [UNESP]; Dalpian, G. M. (American Institute of Physics (AIP), 2014)
We report on density functional theory investigations of the electronic properties of monofunctional ligands adsorbed on ZnO-(10 (1) under bar0) surfaces and ZnO nanowires using semi-local and hybrid exchange-correlation functionals. We consider three anchor groups, namely thiol, amino, and carboxyl groups. Our results indicate that neither the carboxyl nor the amino group modify the transport and conductivity properties of ZnO. In contrast, the modification of the ZnO surface and nanostructure with thiol leads to insertion of molecular states in the band gap, thus suggesting that functionalization with this moiety may customize the optical properties of ZnO nanomaterials. (C) 2014 AIP Publishing LLC.